KUDESAN EFFICACY IN ADOLESCENTS WITH METABOLIC SYNDROME - M.B. Kolesnikova; T.A. Chervinskih ("Paediatrician" Publishers LLC, 2011)
Metabolic abnormalities in metabolic syndrome affect the functioning of practically all organs and systems, and most seriously - cardio-vascular system. Cardio-vascular abnormalities in metabolic syndrome manifest as arterial hypertension, Riley-Day syndrome and endothelial dysfunction that can lead to decrease of adaptive and reserve capabilities. Co-enzyme Q10 possesses cardioprotective,  stress-protective and anti-ischaemic activity. Clinical study performed on 40 children aged 10 to 17 years with constitutive obesity, complicated metabolic syndrome, has proven validity of co-enzyme Q10 treatment in patients with metabolic syndrome. The use of co-enzyme Q10 15 mg/day during 30 days has lead to improvement of psycho-emotional condition, decrease in anxiety complaints, sleep improvement, decrease in asthenic syndrome symptoms, improvement in electrophysiological heart indices Key words: metabolic syndrome, co-enzyme Q10. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 102-106.)